Situated analysis of elite trampolinists' problems in competition using retrospective interviews - Hauw, D.; Durand, M. (Journal of Sports Sciences, 2007)
The aims of this study were to identify and analyse elite athletes' problems in competition. A situated cognition approach placed the emphasis on athletes' actions (i.e. cognitions and behaviours), which were considered to emerge from couplings with selected elements of the context. Fifty-two exercises performed by 10 elite trampolinists were analysed. Field observations, structured interviews, and self-confrontation interviews were conducted and transcribed, and used together with behavioural descriptions derived from video recordings. Performance problems were selected from these reports and from the major infringements of trampoline rules. Qualitative analysis identified the meaningful units of action and their semiotic components for each problem. Four categories of problem were identified and noted to appear either separately or jointly while performing: (a) finding the best moment to begin the performance; (b) finding and maintaining the best mode of involvement to end the performance; (c) recovering normal sensory-motor capacity to perform; and (d) solving problems quickly and definitively while performing. The results suggest that the study of action - situation couplings in sports, as well as of their constantly evolving dynamics, not only reveals elite athletes' psychological activity, but is vital to a deeper understanding of these couplings.